Design and fabrication of self-cleaning eater fish tank filter / Nur Nabila Sofea Mohd Izham - Mohd Izham, Nur Nabila Sofea (2023)
This project is about the design and fabrication of self-cleaning water fist tank filter that can be used for pet owners. The problem with the existing pumps on the market is that there is no self-cleaning system inside the filter. So, it is hard to clean it. Consumers tend to spend a lot of time for cleaning the filter system. Because of that, the idea of fabricating the self-cleaning water fish tank filter that can easier the work and reduce the time for cleaning it. The objective of this project is to create a system to clean the filter automatically. DC motor is used to rotate the filter container that attached with brushes. So, when the container is rotating, the brush will brush all the dirt inside the filter.